Phenotypical heterogeneity in RAG‐deficient patients from a highly consanguineous population. (4th November 2018) - Meshaal, S. S.; El Hawary, R. E.; Abd Elaziz, D. S.; Eldash, A.; Alkady, R.; Lotfy, S.; Mauracher, A. A.; Opitz, L.; Pachlopnik Schmid, J.; van der Burg, M.; Chou, J.; Galal, N. M.; et al.
Summary: Mutations affecting recombination activation genes RAG1 and RAG2 are associated with variable phenotypes, depending on the residual recombinase activity. The aim of this study is to describe a variety of clinical phenotypes in RAG ‐deficient patients from the highly consanguineous Egyptian population. Thirty‐one patients with RAG mutations (from 28 families) were included from 2013 to 2017. On the basis of clinical, immunological and genetic data, patients were subdivided into three groups; classical T – B – severe combined immunodeficiency (SCID), Omenn syndrome (OS) and atypical SCID. Nineteen patients presented with typical T – B – SCID; among these, five patients carried a homozygous RAG2 mutation G35V and five others carried two homozygous RAG2 mutations (T215I and R229Q) that were detected together. Four novel mutations were reported in the T – B – SCID group; three in RAG1 (A565P, N591Pfs*14 and K621E) and one in RAG2 (F29S). Seven patients presented with OS and a novel RAG2 mutation (C419W) was documented in one patient. The atypical SCID group comprised five patients. Two had normal B cell counts; one had a previously undescribed RAG2 mutation (V327D). The other three patients presented with autoimmune cytopaenias and features of combined immunodeficiency and were diagnosed at a relatively late age and with a substantial diagnostic delay; one patient had a novel RAG1 mutation (C335R). PID disorders are frequent among Egyptian children because of the high consanguinity. RAG mutations stand behind several variable phenotypes, including classical SCID, OS, atypical SCID with autoimmunity and T – B + CID. Abstract : RAG1/2 mutations stand behind variable clinical phenotypes.‎ The different phenotypes extend to include T – B + SCID and combined immunodeficiency ‎with granuloma and/or autoimmunity.‎ The genotype–phenotype correlation is not absolute and is affected by epigenetics, early ‎exposure to infections and other environmental factors.